Leadership Development in Academic Health Science Centers: Towards a Paradigm Shift - Brownfield E; Cole DJ; Segal RL; Pilcher E; Shaw D; Stuart G; Smith G (Dove Medical Press, 2020)
Elisha Brownfield,1 David J Cole,2 Richard L Segal,3 Elizabeth Pilcher,4 Darlene Shaw,5 Gail Stuart,6 Gigi Smith7 1Division of General Medicine, Strategic Leadership Development, Medical University of South Carolina (MUSC), Charleston, SC, USA; 2Medical University of South Carolina (MUSC), Charleston, SC, USA; 3Department of Rehabilitation Sciences, MUSC College of Health Professions, Charleston, SC, USA; 4Department of Oral Rehabilitation, MUSC College of Dental Medicine, Charleston, SC, USA; 5Institutional Strategy, Medical University of South Carolina, Charleston, SC, USA; 6MUSC College of Nursing, Charleston, SC, USA; 7MUSC Education Innovation and Student Life, College of Nursing, Charleston, SC, USACorrespondence: Elisha BrownfieldDivision of General Medicine, Strategic Leadership Development, Medical University of South Carolina (MUSC), Charleston, SC 29425, USATel +1 843-876-8547Fax +1 843-792-7285Email brownfe@musc.eduProblem: In an era of increasing complexity, leadership development is an urgent need for academic health science centers (AHSCs). The Association of American Medical Colleges (AAMC) and others have described the need for a focus on organizational leadership development and more rigorous evaluation of outcomes. Although the business literature notes the importance of evaluating institutional leadership culture, there is sparse conversation in the medical literature about this vital aspect of leadership development. Defining the leadership attributes that best align with and move an AHSC forward must serve as the foundational framework for strategic leadership development.Approach: In 2015, the Medical University of South Carolina (MUSC) began a systematic process to approach strategic leadership development for the organization. An interprofessional group completed an inventory of our leadership development programs and identified key drivers of a new institutional strategic plan. A strategic leadership advisory committee designed a series of leadership retreats to evaluate both individual and collective leadership development needs.Outcomes: Three key drivers were identified as critical attributes for the success of our institutional strategy. Four specific areas of focus for the growth of the institution’s ideal leadership culture were identified, with specific action items or behaviors developed for our leaders to model. As a result of this foundational work, we have now launched the MUSC Leadership Institute.Next Steps: Knowledge of our current leadership culture, key drivers of strategy and our desired collective leadership attributes are the basis for building our institutional leadership development strategy. This will be a longitudinal process that will start with senior leadership engagement, organizational restructuring, new programming and involve significant experimentation. Disciplined, thoughtful evaluation will be required to find the right model. In addition to individual transformation with leadership development, MUSC will measure specifically identified strategic outcomes and performance metrics for the institution.Keywords: key drivers, strategic development, collective efficacy, collaboration, courageous authenticity, interprofessional